A GTP synthase ribozyme with increased GTP turnover - Xu Han; Zoe J. Pepper; Joshua T. Arriola; Ulrich F. Müller (Proceedings of the National Academy of Sciences, 2026)
Before the invention of encoded protein translation, early stages of life likely relied on catalytic RNAs (ribozymes). To test how such a system could have functioned, researchers have developed ribozymes that could have provided central functions. The central function of self-replication would have required templated RNA polymerization of nucleotides, which is energetically driven in today’s life forms by the use of nucleoside 5′-triphosphates (NTPs). We previously showed that ribozymes can catalyze the formation of guanosine 5′-triphosphate (GTP) from guanosine and the prebiotically plausible polyphosphorylation reagent cyclic trimetaphosphate (cTmp) by generating a guanosine triphosphorylation ribozyme (GTR) using an in vitro selection in emulsion. This ribozyme (GTR1) had a catalytic rate enhancement of about 18,000-fold but a turnover of only about 1.7. Here, we improved this ribozyme by emulsion selection from a doped library of GTR1 that was metabolically coupled to a polymerase ribozyme. High-throughput sequencing and biochemical analysis identified the most efficient variant of GTR1 with 19 mutations, which increased the GTP turnover number to ~13. Biochemical analysis of this GTR1e revealed biphasic reaction kinetics with an apparent overall K M APP around 11 mM for cTmp. When coupled to an RNA polymerase ribozyme, up to five guanosines were incorporated into an RNA polymer, which represents an important step toward modeling an RNA-based life form in the lab.